Unveiling the Nutritional Quality of the Sicilian Strawberry Tree (Arbutus unedo L.), a Neglected Fruit Species - Litrenta, Federica; Nava, Vincenzo; Albergamo, Ambrogina; Potortì, Angela Giorgia; Sturniolo, Roberto; Lo Turco, Vincenzo; Di Bella, Giuseppa (Foods, 2025)
Although the strawberry tree (A. unedo L.) has been long considered a neglected species of the Mediterranean maquis, the valorization of its fruit production may enhance its socioeconomic value, especially in rural areas. In this study, strawberry trees from different Sicilian sites were investigated in terms of macronutrients, fatty acid (FA) composition, tocopherols, total phenols, carotenoids, and minerals. Sicilian berries were a good source of carbohydrates (mainly fructose, glucose and sucrose) and dietary fiber. They were low in fat; however, the FA composition revealed the abundance of unsaturated FAs over saturated FAs and an advantageous n-6/n-3 ratio. Additionally, Sicilian berries showed an inversed linoleic/α-linolenic acid ratio with respect to berries from other Mediterranean regions, that had previously investigated in literature. This evidence suggests that this ratio may have a chemotaxonomic relevance. Considering antioxidants, the fruits had levels of tocopherols, particularly α-tocopherol, total phenols and carotenoids similar to those of certain commercial fruits. Precious amounts of minerals, such as Ca, K, Zn and Fe were also determined. Interestingly, berries harvested near a Sicilian volcanic area had higher levels of minerals, as well as tocopherols, phenols and carotenoids, than fruits from other Sicilian sites, thereby advancing the hypothesis that fruits from volcanic areas may have a superior nutritional value. Overall, data from this study elaborated by a proper statistical analysis revealed that the geographical origin was a relevant variable to consider in the reliable study of this fruit species.